Recursos literarios en la crónica periodística. - Olmedo Guerrero, Eliana Belén (2016)
The newspaper report maintains a close link with literature, their aesthetic contribution to the narrative of this genre, causes the story visually better appreciated by the reader due to the use of literary devices. For the investigation of the connection between these two fields was raised determine the resources in three chronicles of Colombian journalist Alberto Salcedo Ramos: "The line of Meissen Hospital", "Crossing Wikdi" and "Eternal revelry of Diomedes." This in order to answer the research question posed: Is there more clearly in a journalistic message when literary devices are used? This qualitative research was based on the descriptive method or description of information collected through various techniques such as documentary research, diagrams and tables were organized for reflection, plus a semi-structured interview with the author object of this study. Among the findings it can be concluded that the chronicler Alberto Salcedo Ramos, handles a similar to that of narrative literature; in their stories they can be discovered literary resources that contribute to the content of the text, creating a comprehensive explanation of what is narrated and creating an illusion in the reader's mind about actions, places and events.